Rwanda launches Irrigation Master Plan - Gachene, C.; Oduour, A.; Kipruto, C.; Malesu, M. (2010)
Rwanda’s economy mainly depends on the agricultural sector, particularly food crop production. Poverty reduction therefore largely depends on efforts made on the modernisation of this sector. Although Rwanda possesses considerable water resources, they are not evenly distributed. For example, while water is abundant in the marshlands, facilities for storing it elsewhere for irrigation purposes are lacking. Farming during dry seasons is thus limited in most parts of Rwanda. Agriculture and livestock in the eastern parts of Rwanda, where rainfall is lowest, are especially affected. This situation created a need for a full, efficient and sustainable exploitation of water resources that can help to ensure the sustainable production of food, cash, export and industrial crops.